Early age hydration of model slag cement: Interaction among C3S, gypsum and slag with different Al2O3 contents. (November 2022) - Zhang, Yu; Wan, Zhi; de Lima Junior, Luiz Miranda; Çopuroğlu, Oğuzhan
Abstract: A deeper insight into SO3 /Al2 O3 ratio including the contribution of alumina in slag at early age is required to ensure a properly sulfated slag cement. In this paper, to investigate the effect of gypsum and alumina of slag, emphasis was laid on the hydration characteristics of C3 S-gypsum-slag system during the early age, of which slag was synthesized in the laboratory with varying Al2 O3 contents from 3.69 to 18.19 wt%. The duration of dormant period during the hydration of C3 S depended on Al2 O3 content of slag significantly; however, the amount of silicate reaction before the onset of aluminate reaction was independent of slag chemistry and gypsum content added. The rate of aluminate reaction was controlled by the availability of reactants, SO4 2− and Al 3+ ions in particular, which were sourced from gypsum and slag, respectively. Calcium monosulfoaluminate only occurred in mixture when slag contained a high amount of Al2 O3 (18.19 wt% in this study) at early age, and its formation proceeded continuously at the expense of ettringite. Sulfur rich species incorporated in slag started to participate into aluminate reaction after the main hydration peak of C3 S, and it played a similar role to gypsum.